2008
DOI: 10.3354/esr006087
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian hierarchichal model for evaluating the risk of vessel strikes on North Atlantic right whales in the SE United States

Abstract: A primary factor threatening the recovery of the North Atlantic right whale is the ongoing risk of collision with large ocean-going vessels. Hence, any viable conservation strategy must include mitigation of this risk. In particular, the critical wintering habitat off the Atlantic shores of the southeastern United States overlaps with the shipping routes of some of the region's busiest ports. As a first step in the process of ship strike risk mitigation for this region, we estimated the risk associated with cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…tion boundaries be revisited. While we are not estimating risk of ship strike, previous work has documented the successful reduction in risk of ship strike to right whales with a combination of traffic separation schemes and speed restrictions (Fonnesbeck et al 2008;Vanderlaan et al 2008). Incorporating the results presented here in conservation and management schemes would protect a larger portion of right whale habitat in this critical yet understudied area of their range.…”
Section: Discussionmentioning
confidence: 92%
“…tion boundaries be revisited. While we are not estimating risk of ship strike, previous work has documented the successful reduction in risk of ship strike to right whales with a combination of traffic separation schemes and speed restrictions (Fonnesbeck et al 2008;Vanderlaan et al 2008). Incorporating the results presented here in conservation and management schemes would protect a larger portion of right whale habitat in this critical yet understudied area of their range.…”
Section: Discussionmentioning
confidence: 92%
“…SST for a sampling unit was calculated as the mean of all semimonthly mean SST 1.47 km pixels within each cell. The potential environmental predictors mentioned above were chosen based on previous studies of right whales in the SEUS [5], [8], [9], [10]. Additionally, the semimonthly mean SST data were used to estimate the location of the 22°C SST isotherm (Spatial Analyst in ArcGIS 10.0); this isotherm was chosen because 22°C is at the upper SST range for right whales in this region [5] and can be used as a proxy for the Gulf Stream boundary in winter [19].…”
Section: Methodsmentioning
confidence: 99%
“…If whale distribution can be modeled and predicted from environmental variables and behavioral patterns, management strategies can be developed that take into account system variability and uncertainty. Several predictive habitat models have been developed for the right whale wintering grounds in the SEUS [5], [8], [9], [10]. However, these models did not analyze the most current survey data, including surveys with more consistent protocols (see Methods) and data from the recent SC-GA surveys, which have significantly expanded coverage in the northern section of the wintering ground.…”
Section: Introductionmentioning
confidence: 99%
“…Right whales still travel through the entire management area, and an average of 18% of the NEAq field-based sightings occurred within the recommended routes during the surveys since implementation. However, alternative routing scenarios relative to right whale occurence probabilities were analyzed by Fonnesbeck et al (2008), who found that the option that most closely resembles the current recommended routes reduces the potential encounter rate by 44% compared to no routing.…”
Section: Discussionmentioning
confidence: 99%
“…The relative risk reduction from recommended routing was a function of compliance (96.2%) and the decrease in the likelihood of a vessel and whale encounter (44%; Fonnesbeck et al 2008) times the baseline probability of an encounter (0.57). The relative risk reduction from the recommended routes alone was 54.3%.…”
Section: Yearmentioning
confidence: 99%